Development and scale-up of enhanced polymeric membrane reactor systems for organic synthesis - Zhang, Fan (Kansas State University, 2012)
Reversible organic reactions, such as esterification, transesterification, and acetalisation, have enjoyed numerous laboratory uses and industrial applications since they are convenient means to synthesize esters and ketals. Reversible organic reactions are limited by thermodynamic equilibrium and often do not proceed to completion. High yields for these equilibrium driven reactions can be obtained either by adding a large excess of one of the reactants, which results a reactant(s)/product(s) mixture requiring a separation, or by the selective removal of by-products. Conventional removal techniques including distillation, adsorption, and absorption have drawbacks in terms of efficiency as well as reactor design. Pervaporation membrane reactors are promising systems for these reactions since they have simpler designs, and are more energy efficient compared to conventional downstream separation techniques. This project created a general protocol that can guide one to carry out experiments and collect necessary data for transferring membrane reactor design concepts to the construction of industrial-scale membrane reactors for organic synthesis. Demonstration of this protocol was achieved by (1) experimental evaluation of membrane reactor performance, (2) modeling, and (3) scale-up. The capability of membranes for water/organic separations and organic/organic separations during reversible reactions was investigated. Our results indicated that enhanced membrane reactors selectively removed the by-product water and methanol from reaction mixtures and achieved high conversions for all investigated reactions. Second, modeling and simulation of pervaporation membrane reactor performance for reversible reactions were carried out. The simulated performance agrees well with experimental data. Using the developed model, the effects of permeate pressure and membrane selectivity on membrane reactor yield were examined. Finally, a scale-up on transesterification membrane reactors was carried out. The membrane modules investigated included a bench-scale flat sheet membrane, a bench-scale hollow fiber membrane module, and a pilot-scale hollow fiber membrane module. A 100% conversion was obtained by the selective methanol removal. It is found that with high methanol selectivity membranes, the reaction time to achieve a given conversion continuously decreases with increasing the methanol removal capacity of the reactor system. However, this is a highly nonlinear relationship.
Keywords: Membrane reactor; Modeling; Pervaporation; Transesterification; Acetalisation; Scale-up; Chemical Engineering (0542)